2009
DOI: 10.1021/la9037414
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Resolved Investigation of Solution Cast Nanoparticle Films by X-ray Scattering and Multidimensional Data Set Classification

Abstract: A combinatorial high-throughput approach is used to investigate a solution cast gradient consisting of colloidal gold nanoparticles on top of a silicon substrate by means of a X-ray nanobeam. Classification algorithms are used to reveal and visualize structural transitions from a frozen colloidal solution to a well-defined nanostructure. Prominent length scales on the order of 100 nm are observed. A periodic change in the nanostructure along the gradient is explained by a simplified stick-slip model.The fundam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 35 publications
(70 reference statements)
2
30
0
Order By: Relevance
“…We consider that the clusters continuingly grow and separate each other with a distance ζ in the solvent. This physical configuration is confirmed by the x-ray scattering experiment for drying nanoparticle suspension [15,17]. After k coalescences (k doublet reactions), the number and radius of clusters in the suspension are…”
Section: Colloidal Clusters Coalesce In the Drying Processmentioning
confidence: 53%
See 1 more Smart Citation
“…We consider that the clusters continuingly grow and separate each other with a distance ζ in the solvent. This physical configuration is confirmed by the x-ray scattering experiment for drying nanoparticle suspension [15,17]. After k coalescences (k doublet reactions), the number and radius of clusters in the suspension are…”
Section: Colloidal Clusters Coalesce In the Drying Processmentioning
confidence: 53%
“…[7,15]), which indicates that no flow replenishes solvent loss owing to the evaporation. The particle diffusion from inner suspension to the reaction area (drying front) can be neglected (Appendix subsection B).…”
Section: Colloidal Clusters Coalesce In the Drying Processmentioning
confidence: 99%
“…So far, the minimum demonstrated X-ray beam size in GISAXS experiments is 300 nm and the corresponding experiments are named nanobeam GISAXS (nGISAXS). With a beam diameter of 300 nm, GISAXS measurements have been performed on ordered nanoparticles at the airwater-substrate boundary in colloidal solutions (Roth, Autenrieth et al, 2007) and solution-cast gradients consisting of colloidal gold nanoparticles on top of a silicon substrate (Roth et al, 2010). The use of a high-brilliance 300 nm X-ray beam allows for acquisition times of 120 s per two-dimensional GISAXS pattern and this has enabled in situ investigations such as the nanoscale structuring that occurs during evaporation of water (Roth, Autenrieth et al, 2007).…”
Section: Micro-beam and Nano-beam Gisaxsmentioning
confidence: 99%
“…7 Therefore, much effort has been put into better understanding of the growth process and structural transition of nanocomposites. 8,9 It has been shown that the optical and electrical properties of a metal-polymer film are very sensitive to small changes in the composition and/or morphology of the film and that this sensitivity is drastically increased near the percolation threshold, 10 when a conducting path is formed for the first time.…”
Section: Introductionmentioning
confidence: 99%